2010
DOI: 10.1021/ef901297e
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Athabasca Vacuum Residue Constituents on Synthetic Mineral and Process Equipment Surfaces from Mixtures with Pentane

Abstract: Deposition of organic material on mineral and process equipment surfaces poses production, transport, and refining challenges for the petroleum industry. For high-asphaltene content hydrocarbon resources, such as bitumen, deposits are frequently assumed to be asphaltene rich. In this work, deposits formed from Athabasca vacuum residue (AVR) comprising 32 wt % asphaltenes + pentane mixtures on acidic (FeS, SiO2) and basic (Fe2O3/FeOOH/FeO, Ni/NiO/NiOH) substrates are analyzed using X-ray photoelectron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 86 publications
0
29
0
Order By: Relevance
“…76 Nevertheless, a different behavior has been encountered regarding the acid−base interactions as it has been determined that the initial attractive asphaltene− adsorbent force is dominated by the presence of N-containing functional groups, 77 i.e., the monolayers formed by the initially adsorbed asphaltenes contain more polar species, and the additional layers in a multilayer assembly are formed mainly through van der Waals forces, H-bonding, and π−π stacking. 78 In this regard, sulfur has been established to have a minor role in asphaltene adsorption compared to other species with oxygen and nitrogen in their structure 65,79 and is mainly related to the fact that the nitrogen groups, which are partially positively charged, can produce acid−base interactions with the typically acidized sorbent surfaces. This behavior leads to an increase in asphaltene adsorption as the nitrogen content increases in the oil-heavy fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Nevertheless, a different behavior has been encountered regarding the acid−base interactions as it has been determined that the initial attractive asphaltene− adsorbent force is dominated by the presence of N-containing functional groups, 77 i.e., the monolayers formed by the initially adsorbed asphaltenes contain more polar species, and the additional layers in a multilayer assembly are formed mainly through van der Waals forces, H-bonding, and π−π stacking. 78 In this regard, sulfur has been established to have a minor role in asphaltene adsorption compared to other species with oxygen and nitrogen in their structure 65,79 and is mainly related to the fact that the nitrogen groups, which are partially positively charged, can produce acid−base interactions with the typically acidized sorbent surfaces. This behavior leads to an increase in asphaltene adsorption as the nitrogen content increases in the oil-heavy fractions.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, sulfur has been established to have a minor role in asphaltene adsorption compared to other species with oxygen and nitrogen in their structure , and is mainly related to the fact that the nitrogen groups, which are partially positively charged, can produce acid–base interactions with the typically acidized sorbent surfaces. This behavior leads to an increase in asphaltene adsorption as the nitrogen content increases in the oil-heavy fractions. ,, This increased adsorption is derived from the explained acid–base interactions, which in silica surfaces are enhanced by the presence of hydroxyl Si–OH functional groups (silanol), as the partially positive charged nitrogen species are enabled to interact with the negatively charged silanol groups. …”
Section: Resultsmentioning
confidence: 99%
“…In another study, 37 it was found that the capacity of adsorption of asphaltenes onto illite has a linear correlation with increasing the content of C and S. It has been also reported 84 that for the asphaltenes adsorbed onto basic surfaces present higher concentration of sulfur, however the total adsorbed amount of the asphaltenes was lower compared with the adsorbed amount over acid surfaces which bind more quickly or strongly to lower sulfur-containing species. 19,84 According to Curtis et al, 85 the adsorption of model asphaltenes compounds onto dry silica followed the order phenylsulfoxide > quinoline > phenol > benzoic acid > benzophenone > benzylbenzoate > pyrene. As shown in Figure 4 and Table 2, there is excellent agreement between the SLE-RC model and the experimental results with RMSE% values < 2%.…”
Section: As Shown Inmentioning
confidence: 99%
“…Over the past decade, many studies have examined asphaltene adsorption on minerals. Several studies suggested that in toluene and heptol (mixture of n -heptane and toluene) solutions, asphaltenes or their aggregates did not penetrate into the interlayers of clays and were adsorbed only on their surfaces. , Both monolayer and multilayer adsorption have been observed in experiments. For example, Dudášová et al investigated the adsorption of asphaltenes from five different origins onto minerals and clays (kaolin, CaCO 3 , BaSO 4 , FeS, Fe 3 O 4 , TiO 2 , and SiO 2 ) in heptol and found that the Langmuir isotherm model fitted well to all of the experimental isotherms. Their results indicated that the adsorption of asphaltenes was in the form of a monolayer, and the adsorption capacities were determined to vary from 0.26 to 3.78 mg/m 2 .…”
Section: Introductionmentioning
confidence: 99%